Survival Outcome in Patients with Bilateral Gross Renal Parenchymal Impairment detected by Tc-99m DTPA Renogram (Bangladesh Journal of Nuclear Medicine, 2018)
Introduction: Bilateral gross renal parenchymal impairment (GPI) is a term often used in nuclear imaging to describe severe diffuse glomerular dysfunction obtained with renal scan using Tc-99m diethylene triamine penta-acteic acid (Tc99m DTPA renogram). Whether bilateral GPI found on Tc99m DTPA renogram has any significance on the survival outcome of the patients has not been studied in Bangladesh.Purpose: The study was carried out with the purpose of obtaining a sketch of short-term survival outcome in patients diagnosed with bilateral GPI at National Institute of Nuclear Medicine and Allied Sciences (NINMAS), a tertiary level institute.Method: Nuclear imaging data of patients who had Tc-99m DTPA renogram from January 2013 to June 2013 at NINMAS were obtained from the divisional archive. Total number of patient who underwent the procedure within this period were examined and only those patients with definite diagnosis of bilateral GPI on renal scan were selected for final analysis. Telephone interview was conducted in the year 2015 to obtain the clinical follow-up data of patients with bilateral GPI.Results: In the six months period from January 2013 to June 2013, there were 576 patients who had Tc-99m DTPA renogram. Out of these, 21 patients (M/F=15/6) with mean age 45 ± 20.9 (3 months to 71 years) were diagnosed to have bilateral GPI. Follow up data of 16 (M/F=12/4) patients with mean age 41.2 ± 22.3 (3 months to 65 years) were available. Eleven (68.8%) patients were alive at the time of follow up and five (31.2%) patients were found deceased. Deaths in all were reported to be associated with renal failure and occurred during hospital management. In this patient group, one and two year survival was estimated to be 93.8 and 68.8%.Conclusions: This study is expected to initiate in-depth assessment of survival pattern in kidney diseases in Bangladesh through future research.Bangladesh J. Nuclear Med. 18(2): 135-140, July 2015